Contrasting mechanistic susceptibilities of hematopoietic and endothelial stem-progenitor cells in respective pathogeneses of HIV-1 and SARS-CoV-2 infections - Koka, Prasad S.; Ramdass, Bharathi (Frontiers in Cell and Developmental Biology, 2023)
The multitude of cellular types as expected behave differently when receiving the invading pathogens such as the mammalian viruses. Obviously, the nature-dictated causes for such intrinsic cellular diversity, become the criteria for emergenceof specific virus-receptor interactions of the particular host cellular surface, in order to accommodate various other forms of life whether or not desirable to the host. Currently, we are presented with an example of two contrasting behaviours wherein the earlier detected HIV-1 and the more recently emergent SARS-CoV-2 cause adverse consequences to the differentiation and functions of progenitor stem cells. These include the two different downstream multipotent CD34+ hematopoietic (HSPC) and CD133+ endothelial (ESPC) stem-progenitor cells of their common pluripotent hemangioblast precursors. The two viruses target the respective endothelial and hematopoietic stem-progenitor cells to thrive upon the relevant host cellular surrounded stromal microenvironments, by adopting reciprocally-driven mechanistic routes, which incidentally cause pathogenesis either directly of ESPC (SARS-CoV-2), or indirectly of HSPC (HIV-1). HIV-1 utilizes the CD4+ T-lymphocyte receptor thereby advancing pathogenesis indirectly to the CD34+ HSPC. SARS-CoV-2 directly targets the CD133+ ESPC via ACE2 receptor causing cytokine storms of the CD4+ T-lymphocytes. In this manner, these two viruses cause and extend their damage also to the other cellular sub/types coexisting in the host cellular microenvironments. The infected individuals require clinical interventions that are efficacious to prevent cellular dysfunction and ultimate cell depletion or death. We infer from these viruses mediated pathogeneses mechanisms a potential common origin of microRNA molecular therapies to address cellular dysfunctions and prevent cell loss.